Study by GC-MS method of Thymus x citriodorus (Pers.) Schreb. var. “Silver Queen” extracts component composition - Ya. M. Steshenko; O. V. Mazulin (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2022)
The Thyme L. genus is quite common in Ukraine, herbal extracts are part of many effective herbal medicinal products that are widely used in modern phytocosmetology. Today, genus Thymus x citriodorus (Pers.) Schreb. var. “Silver Queen” is poorly studied but promising in terms of sufficient raw material base and BAS. Therefore, the GC-MS method of designating the component of the extract from herb splint is relevant.